Spinal Myeloid Sarcoma “Chloroma” Presenting as Cervical Radiculopathy: Case Report - Hu, Xiaobang (Global Spine J, 2015)
Study Design Case report. Objective Myeloid sarcoma (also known as chloroma) is a rare, extramedullary tumor composed of immature granulocytic cells. It may occur early in the course of acute or chronic leukemia or myeloproliferative disorders. Spinal cord invasion by myeloid sarcoma is rare. The authors report a rare case of spinal myeloid sarcoma presenting as cervical radiculopathy. Methods A previously healthy 43-year-old man presented with progressive neck, right shoulder, and arm pain. Cervical magnetic resonance imaging (MRI) revealed a very large enhancing extradural soft tissue mass extending from C7 through T1, with severe narrowing of the thecal sac at the T1 level. The patient underwent posterior cervical open biopsy, laminectomy, and decompression. Histologic examination of the surgical specimen confirmed the diagnosis of myeloid sarcoma. Postoperatively, a bone marrow biopsy was done, which showed myeloproliferative neoplasm with eosinophilia. The patient then received systemic chemotherapy and radiotherapy. Results At the 10-month follow-up, the patient reported complete relief of arm pain and neck pain. X-rays showed that the overall cervical alignment was intact and there was no evidence of a recurrent lesion. MRI showed no evidence of compressive or remnant lesion. Conclusions Spinal myeloid sarcoma presenting as cervical radiculopathy is rare, and it may be easily misdiagnosed. Knowledge of its clinical presentation, imaging, and histologic characterization can lead to early diagnosis and appropriate treatment.